Evaluating Presence Data versus Expert Opinions to Assess Occurrence, Habitat Preferences and Landscape Permeability: A Case Study of Butterflies - Muhammad Arfan (Environments, 2018)
We explored how presence data and expert opinions performed with respect to identifying the ecological preferences and the spatial needs of six butterfly species in the Federal State of Saxony, Germany. We used presence records and a land-cover map. In parallel we used expert responses to evaluate the 40 land-cover types occurring in the map, in terms of both suitability and permeability for the six species. Presence data were translated into preferences through Ivlev’s electivity indices (IEI). Visual analysis of preference maps based on IEI showed a distinct pattern of suitable versus less suitable areas. Similarly, spatial analyses found that presence-points were closer to suitability areas based on IEI than those that were based on expert data. However, in case of mismatches between expert and presence-based evaluations, independent experts identified the expert evaluation as better and considered IEI outcomes as wrong. We found a medium to high correlation between land-cover class suitability and permeability based on expert opinions for all species. This indicates that expert evaluation of permeability is affiliated with habitat suitability. Integration of species-presence data and expert-knowledge about species could enhance our capabilities to understand and potentially map suitability while gathering information about suitability and permeability separately can improve species conservation planning.